2018
DOI: 10.2147/phmt.s159766
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial sensitivity pattern of urinary tract infection among children with cerebral palsy, Moshi, Tanzania

Abstract: BackgroundUrinary tract infection (UTI) in children with cerebral palsy (CP) is a challenging yet common clinical condition. Children with CP bare the greatest risk of contracting UTI because of their difficulties in neuromotor control which lead to delay of bladder control, causing incomplete bladder emptying and urine retention.MethodThis was an analytical cross-sectional study that was conducted from September 2016 to March 2017 at Comprehensive Community Based Rehabilitation in Tanzania – Moshi and Kiliman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 29 publications
(43 reference statements)
2
26
1
Order By: Relevance
“…Likewise, resistance to ampicillin and cotrimoxazole was high, but only 11% of E. coli isolates displayed resistance to ciprofloxacin, which is lower than we observed in our study. Similar findings were reported from an analysis of UTIs in Tanzanian children with cerebral palsy [12], in people living with human immunodeficiency virus (HIV) infection [13] and in pregnant women [14]. Another prospective study from a northern area of the country identified the diagnosis of UTIs as being significantly associated with E. coli bloodstream infections, which underlines the possible severe consequences of untreated or inadequately treated infections [15].…”
Section: Discussionsupporting
confidence: 67%
“…Likewise, resistance to ampicillin and cotrimoxazole was high, but only 11% of E. coli isolates displayed resistance to ciprofloxacin, which is lower than we observed in our study. Similar findings were reported from an analysis of UTIs in Tanzanian children with cerebral palsy [12], in people living with human immunodeficiency virus (HIV) infection [13] and in pregnant women [14]. Another prospective study from a northern area of the country identified the diagnosis of UTIs as being significantly associated with E. coli bloodstream infections, which underlines the possible severe consequences of untreated or inadequately treated infections [15].…”
Section: Discussionsupporting
confidence: 67%
“…In the current study the percentage of Pus cells and Crystals was higher among CP children and urine culture was positive in 17.5% of cases indicating urinary tract infection in those children. This agrees also with other studies such as Ryakitimbo et al [38] The study included all children aged 2-18 years who were diagnosed to have CP (99 children with CP). UTI was detected in 13.1% of cases.…”
Section: Discussionsupporting
confidence: 91%
“…Excessive secretions due to GER or swallowing disorders, inefficient coughing will lead to an inefficient clearance of secretions and thus favour respiratory infections. 22 UTI was revealed in 9% of cases, which is not very different from the prevalence of Ryakitimbo et al 23 in Tanzania in 2018, which was 13.1%. Constipation would have an impact on the occurrence of urinary tract infection.…”
Section: Discussioncontrasting
confidence: 54%
“…24 Factors that increase the risk of acquiring urinary tract infection in CP include low cognition, limited ability to communicate the need to void, impaired mobility, and bladder dysfunction. 23 Patients with GMFCS V were at greater risk of developing nutritional disorders and orofacial dyspraxia. Indeed, Bearden et al 12 found that malnutrition is more frequent in subjects with GMFCS≥IV.…”
Section: Discussionmentioning
confidence: 99%